Pengaruh Audit Internal dan Manajemen Risiko Terhadap Kinerja Perusahaan dengan Basis BSC - Vitasya Utami Marsu Marsa; Ahmad Syarief; Riauli Susilawaty Hutapea (Indonesian Accounting Literacy Journal, 2022)
The study aims to determine the impact of Internal Audits and Risk Management on company performance. The study was held at PT Perkebunan Nusantara VIII (Persero) also the respondents of this study is from the Unit of Internal Supervisory (SPI) and the Finance and Accounting Unit using non-probability sampling techniques. Furthermore, the data will be processed with the help of SPSS software version 25.0 . The results of the study show that Internal Audit and Risk Management simultaneously have a positive and significant impact on the Company's performance of PT. Perkebunan Nusantara VIII (Persero) is 75.4%. The rest of impacted variables was 24.6% can be influenced by other variables that are not used but still have a relation with this study.